2022
DOI: 10.1039/d2fd00039c
|View full text |Cite
|
Sign up to set email alerts
|

The unimolecular decomposition of dimethoxymethane: channel switching as a function of temperature and pressure

Abstract: Branching ratios of competing unimolecular reactions often exhibit a complicated temperature and pressure dependence that makes modeling of complex reaction systems in the gas phase difficult. In particular, the competition...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Considering the less than 100 μs residence time of the sample in the heated region of the pyrolysis microreactor, the absolute rate constants are too low to account for the observed conversion of the sample. This is consistent with the findings of Pazdera et al, who calculated dimethoxymethane decomposition rate constants, which also appear to be too low for the reaction to proceed significantly in the heated zone 78 . Photoelectron spectroscopy and dissociative ionization experiments have shown that the rovibrational cooling in the expansion is negligible after the sample leaves the reactor 24 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Considering the less than 100 μs residence time of the sample in the heated region of the pyrolysis microreactor, the absolute rate constants are too low to account for the observed conversion of the sample. This is consistent with the findings of Pazdera et al, who calculated dimethoxymethane decomposition rate constants, which also appear to be too low for the reaction to proceed significantly in the heated zone 78 . Photoelectron spectroscopy and dissociative ionization experiments have shown that the rovibrational cooling in the expansion is negligible after the sample leaves the reactor 24 .…”
Section: Resultssupporting
confidence: 90%
“…This is consistent with the findings of Pazdera et al, who calculated dimethoxymethane decomposition rate constants, which also appear to be too low for the reaction to proceed significantly in the heated zone. 78 Photoelectron spectroscopy and dissociative ionization experiments have shown that the rovibrational cooling in the expansion is negligible after the sample leaves the reactor. 24 Therefore, unimolecular reactions may proceed further during the approximately 1 ms collision-free flight time from the reactor exit to the ionization region.…”
Section: Kineticsmentioning
confidence: 99%
“…We note that this simple picture, which may apply to the pyrolysis of MF (see below), is not generally true. As was shown for the thermal decomposition of dimethoxymethane, complications can arise due to entropic effects, resulting in channel switching from energetically low-lying molecular elimination channels to higher-lying bond dissociation channels with increasing temperature and pressure. We further note that we did not include in our calculations excited electronic states, which were discussed to play a certain role in the combustion chemistry of the OCHO radical. , On the one hand, little is known about the thermochemistry and kinetics of these excited states, and on the other hand, decomposition of OCHO is comparatively fast already in the electronic ground state (see below).…”
Section: Introductionmentioning
confidence: 97%